2005
DOI: 10.1590/s0103-50532005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and tautomeric studies of enamines from 1-(n-Hexyl)-3-methyl-2-pyrazolin-5-one

Abstract: 1-(n-Hexil)-3-metil-2-pirazolin-5-ona foi acilada com cloretos de acidos e a condensação com aminas primárias forneceu uma série de enaminas. De acordo com os dados de RMN de 1 H e 13 C, os derivados acilas têm principamente uma estrutura 4-acilpirazol-5-ol com ligação de hidrogênio intramolecular e os derivados 4-aminometilenos existem predominantemente na forma de enamina estabilizada também por este tipo de interação. 1-(n-Hexyl)-3-methyl-2-pyrazolin-5-one was acylated with acid chlorides. Condensation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…The protonated ligand LH (Belmar et al, 2004(Belmar et al, , 2005; 0.1 g, 0.32 mmol) and Cu(O 2 CCH 3 ) 2 ÁH 2 O (0.032 g, 0.16 mmol) were dissolved in ethanol (10 ml) and heated under re¯ux for 1 h. The solution was then evaporated to a ®nal volume of 5 ml and allowed to cool to room temperature. The solid was ®ltered off and crystallized by slow evaporation from a chloroform±hexane mixture (1:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protonated ligand LH (Belmar et al, 2004(Belmar et al, , 2005; 0.1 g, 0.32 mmol) and Cu(O 2 CCH 3 ) 2 ÁH 2 O (0.032 g, 0.16 mmol) were dissolved in ethanol (10 ml) and heated under re¯ux for 1 h. The solution was then evaporated to a ®nal volume of 5 ml and allowed to cool to room temperature. The solid was ®ltered off and crystallized by slow evaporation from a chloroform±hexane mixture (1:…”
Section: Methodsmentioning
confidence: 99%
“…More recently, with the aim of studying the tautomerism involved, it was shown that pyrazolone could be easily alkylated at N1 with primary alkyl halides (Bartulin et al, 1992(Bartulin et al, , 1994Belmar et al, 1997Belmar et al, , 1999. This procedure ®nally allowed the obtention of several enamines derived from 4-acyl-1-nhexyl-3-methyl-5-pyrazolones (Belmar et al, 2004(Belmar et al, , 2005 and even some nitride complexes using these ligands (Pe  rez et al, 2005). In addition to these reports, papers by Maurya et al (1992) and Dey et al (1999) described some complexes using 1-phenylpyrazolone-based imines.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…their greater solubility), most literature reports deal with 1-phenylpyrazolones or N-1 unsubstituted pyrazolones, and only recently has research aimed at synthesizing 1-alkylpyrazolones and derivatives been undertaken (Bartulin et al, 1992(Bartulin et al, , 1994Belmar et al, 1997Belmar et al, , 1999, paying particular attention to the study of the tautomerism involved. These efforts ®nally led to the title enamines, (I) and (II), derived from 4-acyl-1-(n-hexyl)-3-methyl-5pyrazolones (Belmar et al, 2004).…”
Section: Commentmentioning
confidence: 99%
“…The reaction of phenylpyrazolone with trimesoyl chloride afforded a hexadentate chelating ligand that was used in the synthesis of some highly complex organo‐inorganic supramolecular structures. Besides, diamines have been used to anchor 4‐acylpyrazolones through the formation of diimines , and in the field of pigments and dyes, aryldiamines have been used to anchor the heterocyclic to aromatic rings by bis ‐diazotization .…”
Section: Introductionmentioning
confidence: 99%